Decoding the partitioning behavior of poly- and perfluoroalkyl substances: Insights from human liver and blood biomonitoring with machine learning - Linping Cao; Yishu Zheng; Wenfei Yu; Jiaqi Shao; Yu Fu; Yating Liu; Weichen Zhang; Jiamian Fang; Yuanchen Chen; Hangbiao Jin (Environmental Pollution, 2026)

Recent advances in membrane materials for efficient xylene isomers separation - Yating Zhu; Yinghui Xu; Fengkai Wang; Jie Li; Naixin Wang; Quan-Fu An (Chemical Engineering Journal, 2026)

A specific strategy for accelerating strength-development rate of self-generated proppants: the gel effect related autoacceleration - Xianyan Ren; Zhenyong Li; Yating Chen; Xiaoji Fu; Yirui Zhang; Dan Fang; Xirui Chen; Cheng Bian (Fuel, 2026)

Social context modulates the behavioural effects of physical enrichment in yellowfin seabream Acanthopagrus latus - Yijie He; Zonghang Zhang; Yating Zheng; Wuhan Lin; Wentao Lu; Qiaoling Fu; Wenhua Liu (Applied Animal Behaviour Science, 2026)

Heteroatom-doped MXene quantum dots: red emission tuning and dual-functional performance - Fanyong Yan; Ruixue Bai; Yating Li; Shanshan Li; Jinyun Xu; Juanru Huang; Yu Wang; Yang Fu (Analytica Chimica Acta, 2026)

No clear preferences for the lineal sex: A comparative study on the differences in progression of parity - Baisensen Zhang; Haiying Zhang; Yating Liu; Chang Fu; Qiao-Qiao He (Behavioral Ecology and Sociobiology, 2026)

Synchronous enhancement of radical and non-radical pathways in Fenton-like reaction mediated by CuCo bimetallic heterostructure - Jing Zhang; Yating Fu; Ye Liu; Yi Ren; Xingxing An; Bo Lai (Chemical Engineering Journal, 2026)

Microbial biosynthesis of fruit-like aroma compounds: Strategies and challenges toward sustainable food flavor production - Yufeng Wang; Junfeng Wu; Nan Wang; Bohai Zhang; Jianxin Dong; Yating Liu; Mingqin Zhao; Bo Fu (Food Research International, 2026)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Piperazine concentration-driven effect fabricated NF membrane with ambidextrous selectivity for SO42−/Cl− and Mg2+/Na+: Mechanism and efficient water purification - Hailin Chang; Shilei Fu; Ziao Zhang; Yating Hu; Zijian Cui; Jun Ma; Kexin Hou; Xiaobin Tang; Guibai Li; Heng Liang (Desalination, 2025)

The BBX Gene Family in Papaya (Carica papaya L.): Genome-Wide Identification and Expression Profiling During Fruit Ripening - Meiling Ding; Shengjie Li; Jialin Hu; Sicheng Bai; Xianqi Fu; Zhimiao Liang; Xiaomin Liang; Yating Li; Miaoyu Zhao (Tropical Plant Biology, 2025)

Motif-based structural analysis and resilience assessment of the RCEP shipping network - Keyu Xu; Jiaguo Liu; Yating Fu (Ocean & Coastal Management, 2025)

Synergistic effects of metal‑carbon composites in catalytic ozonation: Structure, catalytic pathway and application - Jing Zhang; Kexin Tian; Ye Liu; Yating Fu; Yi Ren; Bo Lai (Chemical Engineering Journal, 2025)

Identification of chemical composition and prediction of in vitro anti-inflammatory activity mechanism of ethyl acetate fraction of Lagenaraia siceraria seed - Yurong Wang; Xiaoyu Fu; Shuyu Xu; Xianyan Li; Siyu Zhao; Yating Zheng; Nanping Jiang; Xin Chen; Xing Wang; Hezhong Jiang (Natural Product Research, 2025)

Amazon Basin shows reduced forest loss but increased forest spatial fragmentation in 1992–2020 - Yating Du; Guangyao Gao; Xue Ma; Shiqin Xu; Bojie Fu (Science of The Total Environment, 2025)

Evaluation of muscle quality and movement-related traits in two common carp strains under a rice–fish farming system - Yating Gong; Mingkun Luo; Xianbo Zhang; Ning Qin; Wenbin Zhu; Lanmei Wang; Jianjun Fu; Zaijie Dong (Aquaculture International, 2025)

Growth Onset Rather Than Photosynthesis Strongly Regulates Autumn Senescence Termination Besides Climate Change - Shuping Ji; Shilong Ren; Yann Vitasse; Constantin M. Zohner; Yongshuo H. Fu; Xiaoqiu Chen; Xiaoyang Zhang; Charlotte Grossiord; Huiying Liu; Matthias Peichl; Dailiang Peng; Shuai An; et al. (Global Ecology and Biogeography, 2025)
Aim Plant senescence largely influences the global carbon cycle by regulating the growing season length. However, the driving mechanisms of plant senescence remain unclear, particularly the role of developmental factors. This study aims to investigate how environmental and developmental factors drive autumn senescence and evaluate whether woody and herbaceous plants exhibit divergent responses to these drivers. Location Eurasia. Time Period 1982–2014. Major Taxa Studied Woody and herbaceous species. Methods Using 120,833 long‐term ground phenological observations, we employed partial correlation analysis to investigate the influence of environmental and developmental factors on senescence termination. Experimental records from literature and pasture survey observations from China were separately utilised to further validate the influence of developmental factors on senescence termination. Structural equation modelling was applied to analyse the pathways of growth onset affecting senescence termination. Additionally, multiple linear regression was used to examine the tendency of the sensitivity of senescence termination to plant development rate. Results We find that earlier growth onset primarily leads to earlier senescence termination directly in herbaceous plants, but indirectly in woody plants by accelerating early‐season development. The sensitivity of senescence termination to plant development rate shows a declining trend, particularly in early‐season negative effects on woody plants and late‐season positive effects on herbaceous plants, suggesting diminished impacts of future warming on senescence timing. The impact of growing season photosynthetic activity on senescence termination is not pronounced for both woody and herbaceous plants. Main Conclusions The results demonstrate that growth onset may affect woody and herbaceous senescence termination through different pathways, whereas the carry‐over effects of growing season photosynthetic activity are not widely discovered. This emphasises that the introduction of developmental factors into phenological models needs to be considered carefully according to plant type.

Unraveling the complexities of ozone and PM2.5 pollution in the Pearl River Delta region: Impacts of precursors emissions and meteorological factors, and effective mitigation strategies - Yating Chen; Liye Zhu; Sihui Wang; Daven K. Henze; Tzung-May Fu; Lin Zhang; Xiaoling Wang (Atmospheric Pollution Research, 2025)

How climate risks relate to Chinese green finance markets in time-frequency domains? A consideration of extreme market conditions - Rongyan Liu; Lingyun He; Ling Chen; Yating Fu (Journal of Cleaner Production, 2025)

Are the impacts of uncertainties on clean and conventional energy markets symmetrical? A fresh comparison analysis based on direction, quantile, and time-domain - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu (Environment, Development and Sustainability, 2024)

Effects of Intestinal M Cells on Intestinal Barrier and Neuropathological Properties in an AD Mouse Model - Shijing Wu; Li Hu; Yiwei Fu; Yating Chen; Zhibin Hu; Huiliang Li; Zhou Liu (Molecular Neurobiology, 2024)

Resilience analysis of the RCEP shipping network - Jiaguo Liu; Yating Fu; Kangkang Han; Ying Cui (Ocean & Coastal Management, 2024)

A green europium-cerium redox flow battery with ultrahigh voltage and high performance - Yating Wu; Lei Zhou; Yangyang Xie; Yaobin Lai; Shangwan Fu; Xingchen Kang; Wenhui Shi; Jian Li; Xuxia Zhang; Kang Hu; Hui Zhang; Tao Qi (Chemical Engineering Journal, 2024)

Oxaliplatin lipidated prodrug synergistically enhances the anti-colorectal cancer effect of IL12 mRNA - Hui Liu; Yating Du; Desheng Zhan; Wenjun Yu; Yan Li; Aiping Wang; Jianpeng Yin; Haiqiang Cao; Yuanlei Fu (Drug Delivery and Translational Research, 2024)

Transition towards sustainable diets: Multi-objective optimization of dietary pattern in China - Haiyue Fu; Yating Li; Penghui Jiang; Shuai Zhou; Chuan Liao (Sustainable Production and Consumption, 2024)

Research advances on microplastics contamination in terrestrial geoenvironment: A review - Mingdong Li; Zhicheng Wang; Liping Zhu; Yating Zhu; Jinxiang Yi; Xiaojie Fu (Science of The Total Environment, 2024)

Research on the economic agents' green co-evolution of China: Framework, model, and application - Ling Chen; Lingyun He; Rongyan Liu; Yating Fu; Quanhui Yang (Journal of Cleaner Production, 2024)

Analyzing the impact of natural capital on socio- economic objectives under the framework of sustainable development goals - Yating Dai; Yuze Ding; Shuya Fu; Lixin Zhang; Jian Cheng; Daolin Zhu (Environmental Impact Assessment Review, 2024)

Physiological and molecular mechanisms of boron in alleviating cadmium toxicity in Capsicum annuum - Chuang Shen; Huiling Fu; Baifei Huang; Qiong Liao; Yingying Huang; Yanbin Wang; Yating Wang; Junliang Xin (Science of The Total Environment, 2023)

Facilely adjusting acidity features of zeolites by steaming treatment for enhanced methanol conversion to aromatics: A mechanism study - Zhenjun Xu; Tingjun Fu; Yating Han; Zhong Li; Guowu Zhan (Fuel, 2023)

Field experiment and numerical simulation for airflow evaluation in a data center with row-based cooling - Yating Wang; Xuelian Bai; Yusen Fu; Yu Tang; Chaoqiang Jin; Zuoyang Li (Energy and Buildings, 2023)

Integrative analysis uncovers the mechanism underlying the environmental adaptation of an indigenous crucian carp (Carassius auratus gibelio) in Dong's Rice Fish Duck System - Mingkun Luo; Xianbo Zhang; Wenbin Zhu; Qianwen Min; Jinli Hu; Jianjun Fu; Xiulan Shi; Bingjie Jiang; Yating Gong; Lanmei Wang; Ting Liu; Zaijie Dong (Aquaculture, 2023)

Antifungal and Biocontrol Evaluation of Four Lysobacter Strains Against Clubroot Disease - Lina Fu; Hanmei Li; Lanfang Wei; Jun Yang; Qi Liu; Yating Wang; Xing Wang; Guanghai Ji (Indian Journal of Microbiology, 2018)

The fungicide difenoconazole alters mRNA expression levels of human CYP3A4 in HepG2 cells - Liumeng Pan; Liping Lu; Jingpeng Wang; Cunwu Zheng; Yujie Fu; Siyuan Xiao; Yating Jin; Shulin Zhuang (Environmental Chemistry Letters, 2017)